La participation des aporoi aux guerres serviles sous la République romaine et leur relation avec les esclaves révoltés. Idéologie dominante, praxis populaire et discordes civiles - Piantanida, Fernando Martín
The participation of free men in the movements led by rebellious slaves sets a complex problem in terms of the importance of the freedom/slavery antinomy in the thinking of the ancient Greeks and Romans. The chattelslaves, defined as things, were represented as foreigners. The slaves served as the 'Others' against which all citizens, from the rich slave owners to the poor artisans and peasants, defined themselves as a unity. The contrast between the slave and the citizen made it possible to shade, from an ideological point of view, the relations of exploitation and the differences of wealth between the citizens. This tended to suppress the social conflict between them. Despite the significant legal and political differences between the free and the enslaved, and the ideological representation that was made of it, the sources narrate that some free men not only did not repress the rebel slaves in the great servile revolts, in solidarity with their rich fellow citizens, but they plundered these last ones or joined the fugitives. In the present work, we study the participation of impoverished free men (aporoi) in the laterepublican servile wars and the relationship they established with the rebel slaves, a problem that has sometimes been neglected by the historiography or only partially treated. Some historiographical currents neglected the participation of the aporoi in the servile wars, and others overestimate it. In opposition, we revalue a line of investigation that, on the one hand, maintains the servile nature of the insurrections, since, the main role was apparently of the rebel slaves, but on the other hand affirms that the participation of free men was an important element. We believe that this point of view is the most appropriate for the testimonies of the sources and we contribute elements to rethink it. Those elements include: to focus the study within the framework of the classic democratic imaginary that will tend to promote the citizen solidarity facing the servile threat; to analyse each revolt individually to evaluate the relationship between the subaltern sectors; and understand the participation of the aporoi, either its parallel rebellion or its inflow to the rebel ranks, as the symptom of tensions within the citizen body that can be defined in terms of stáseis (civil discords), of which the servile revolts nurtured from the beginning. Therefore, the participation of the aporoi is a factor, among others, that helped the growth of the servile revolts. In the case of the first Sicilian revolt and the revolt of Spartacus, we maintain the existence of a conjunctural alliance between the rebellious slaves and the aporoi. In contrast, in the second Sicilian revolt, we defend the interpretative line that supports the idea that there was no relationship between the two groups, but rather two parallel revolts: the free poor simply took advantage of the opportunity in the servile revolt to plunder the properties of the rich. Our work attempts to nuance the most rigid theoretical views that affirm the absolute incommunicability between plebeians and slaves. There were occasions, albeit unusual, where the abyss that separated the free man from the slave did not seem to be so great, at least not to the aporoi, who ignored the imaginary that pitted them against the dishonored social dead. The servile wars were one of those cases.